2019
DOI: 10.12911/22998993/105473
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Water Consumption in the Campus of Warsaw University of Life Sciences - SGGW in Years 2012-2016

Abstract: On the basis of the registered indications of the water meter, a study on the size and variability of water consumption on the WULS campus in the academic years 2012/16 is presented. The average specific water consumption at a time when classes are implemented amounted to 26.6 dm 3 per student per day for full-time studies student and 19.7 dm 3 per student per day for the student part-time studies. During the holiday season, the rates are lower at 18.4 and 11.8 dm 3 per student per day, respectively. These rat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 9 publications
0
9
1
Order By: Relevance
“…Most of the studies found in the literature deal with residential buildings. In fact, the literature survey conducted identified 9 studies on the consumption of water (Abdelalim et al, 2015;Bonnet et al, 2002;Marinho et al, 2019;Meireles et al, 2014Meireles et al, , 2018Wichowski et al, 2019;Zhou et al, 2013) and 17 on the energy consumption (Abdelalim et al, 2015;Amber et al, 2017;Bonnet et al, 2002;Escobedo et al, 2014;Hong et al, 2011;Khoshbakht et al, 2018;Wang, 2016;Ward et al, 2008;Zhou et al, 2013) in university buildings that used different methodologies.…”
Section: Consumption In University Buildingmentioning
confidence: 99%
“…Most of the studies found in the literature deal with residential buildings. In fact, the literature survey conducted identified 9 studies on the consumption of water (Abdelalim et al, 2015;Bonnet et al, 2002;Marinho et al, 2019;Meireles et al, 2014Meireles et al, , 2018Wichowski et al, 2019;Zhou et al, 2013) and 17 on the energy consumption (Abdelalim et al, 2015;Amber et al, 2017;Bonnet et al, 2002;Escobedo et al, 2014;Hong et al, 2011;Khoshbakht et al, 2018;Wang, 2016;Ward et al, 2008;Zhou et al, 2013) in university buildings that used different methodologies.…”
Section: Consumption In University Buildingmentioning
confidence: 99%
“…The solar thermal energy system is designed using 20 flat-plate collectors with an overall gross area of 40 m 2 to cover a daily consumption of hot water of 1500 L/day for 52 students. The average specific water consumption amounted to 26.6 L per student per day for full-time-studies students [26]. The geothermal borehole field is designed using 4 boreholes, with a depth of 50 m each.…”
Section: Energy Efficiency Measuresmentioning
confidence: 99%
“…For sizing the distribution network and other supporting objects in the water supply system, the basic input parameter for sizing is the maximum hourly water consumption Q max,h representing the product of water consumption on the day of maximum consumption (Q max,day ) and the hourly non-uniformity coefficient C h,max [9] . 0,00 1,00 2,00 3,00 4,00 5,00 6,00 7,00…”
Section: Unevenness Of Water Consumption In the Settlementmentioning
confidence: 99%